Analysis of Scientific Activities in the Field of Information Science: the case of Croatia - Lazić, Nikolaj; Lazić - Lazić, Jadranka (Qualitative and Quantitative Methods in Libraries; 2015: Special Issue: Bibliometrics, 2017)
The journal is the basic medium of scientific communication and one of the most widely used sources for bibliometric analysis. In this paper, we will address the scientific activities in the field of information science in Croatia by means of bibliometric analysis of 1418 papers published in social sciences journals listed as references for promotion of scientists through academic ranks in the field of information science. Based on a list of scientific journals and specificity of scientific publishing in national and international scientific journals we will show trends of scientific activities. When it comes to the evaluation of scientific papers it is not the same whether the paper is published in national or international journals. A paper published in a national journal in native language is not evaluated the same (no matter how highly rated paper is) as the paper published in an international journal. For small countries and their languages (which we certainly belong to) an important indicator of the value of the journal is its representation in relevant databases. The possibility that a journal published in national language by an undersized publisher from a small country will enter relevant databases is certainly not the same as in cases when the journal is published in English by a large publisher from a country with strong scientific tradition. The majority of countries where English is not native language seek representation, visibility and recognition through its scientific production in citation indexes. This recognition is measured by the presence of national journals in citation indexes. By the analysis of SSCI, which consists of journals from around the world and all disciplines, we will show the dominance of journals published in English speaking countries and also journals published by major publishers. So actually national journals whose publishers are "small" have no chance of survival because in the evaluation of scientific excellence needed for the academic promotion they have "little" value and are thus avoided by scientists. If we are planning to stimulate our own scientific production in our national language it is necessary to set the criteria which will particularly evaluate papers published in national language when planning scientific policy and the development of science. The purpose of this study is to highlight the need for a new evaluation model and stimulate scientific research in the field of information science in the national context.